Effects of teacher training programme on teachers’ awareness and readiness in secondary inclusive classrooms in Penang / Susila S. Marimuthu - Susila , S. Marimuthu (2018)
In the current inclusive practices of most secondary schools in Malaysia, the regular teachers have not been equipped with the necessary information about the characteristics and learning abilities of the students with disabilities who are included into the regular classrooms. Consequently the researcher of this study, proposed a Teacher Training Progrmme for general educators who teach students with special needs included in their classrooms. The proposed programme comprised five modules that covered significant aspects of inclusive education and disabilities. The programme was evaluated by three experts in the field of special education from the Faculty of Education, University of Malaya and changes suggested by an external expert from the University of The quasi experimental design was chosen as the study utilised intact groups in two chosen secondary schools, with thirty three general educators who teach in the inclusive setting for the experimental and the control groups respectively. The instrument was in the form of a questionnaire consisted of seventy-two items which tested on the domains of awareness that comprised factors of knowledge and values; and domains of readiness that comprised factors of skills and emotions. The Cronbach’s Alpha indicated an internal consistency of 0.917. Both the tests of Kolmogrove- Smirnova and Shapiro-Wilk indicate normality in the distribution as the significant level was greater than 0.05. The findings show that there was significant difference in terms of knowledge before and after the intervention for the Experimental Group, with t(58)=3.41, p<.05. However, there was no significant difference in the factor of values, with t(58)=-.67, p>.05. This indicates that teachers’ awareness in iv terms of knowledge has increased significantly after the intervention for the Experimental Group. The findings further show that there were significant increases in the factor of skills, with t(58)=-2.59, p<.05 and in the factor of emotions, with t(58)=-2.75, p<.05. These indicate that teachers’ readiness in terms of skills and emotions have been enhanced significantly after the intervention. However, when comparing teacher awareness between the Experimental and the Control groups after the intervention, there was no significant difference for the factor of knowledge, with t(57)= -1.63, p>.05, as well as for the factor of values, with t(58)= -1.89, p>.05. The finding, though not significant, does indicate that the Experimental Group had experienced certain level of changes in awareness. As for the comparison of teacher readiness between the Experimental and the Control groups, there was no significant difference for the factor of skills, with t(57)= -1.63, p>.05, as well as for the factor of emotions, with t(58)= -1.89, p>.05. Although the result was not significant, it was in favour of the Experimental Group. The observation of a teacher and the evaluation of the presentation by the Experimental Group were reassuring. It can be concluded that the Teacher Training Programme (TTP) has provided benefits to teachers who have students included in their classrooms.